2020
DOI: 10.1017/s0144686x20001609
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy and age-related health-care utilisation: a multi-dimensional approach

Abstract: Inefficient health service utilisation puts pressure on health systems and may cause such negative individual consequences as over-medicalisation or exacerbation of health problems. While previous research has considered the key relevance of health literacy (HL) for efficient use of health services, the results of that research have been somewhat inconclusive. Possible reasons for diverging results of prior research may be grounded in different measurement concepts of HL and the disregarding of age-specific ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…A two-part hurdle procedure was used in this study to ascertain the major parameters influencing WTP for treatment of hopeless teeth [ 15 ]. This approach is capable of dealing with extremely skewed count data with an excess of zeroes [ 16 ]. The first section employed logistic regression to estimate the chance of WTP for the treatment of a hopeless tooth.…”
Section: Methodsmentioning
confidence: 99%
“…A two-part hurdle procedure was used in this study to ascertain the major parameters influencing WTP for treatment of hopeless teeth [ 15 ]. This approach is capable of dealing with extremely skewed count data with an excess of zeroes [ 16 ]. The first section employed logistic regression to estimate the chance of WTP for the treatment of a hopeless tooth.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, Gerich et al ( 2022 ) indicated that, in the presence of low health-related knowledge, high HL can lead to more frequent doctor visits than low HL. They also referred to studies using registered data, which showed different results for different types of health services.…”
mentioning
confidence: 94%
“…Recent publications have listed numerous studies indicating more efficient use of health care services among people with higher HL. Gerich et al ( 2022 ) reported on research that showed lower medication costs, number of doctor visits, and hospitalization for people with higher HL. Moreover, Berens et al ( 2018 ) cited studies showing higher health service use among individuals with lower HL.…”
mentioning
confidence: 99%
“…Users of primary healthcare services are predominantly of older age ( Gerich et al, 2020 ; Rennemark et al, 2009 ). As older people more often need regular medical treatment due to aging-associated chronic conditions such as hypertension, chronic bronchitis/COPD, or coronary heart disease ( OECD, 2019 ), they are likely more affected by reduced healthcare access.…”
Section: Introductionmentioning
confidence: 99%